Synthesis and characterization of electroless Ni–W-Ce-P coating on AISI 1010 substrate. (2022) - Kumar, Vikash; Baran Mandal, Biplab; Oraon, Buddhadeb
Abstract: A successful quaternary electroless coating of Ni–W–Ce–P on a low carbon steel substrate with superior mechanical and microstructural properties has been deposited. The surface morphology, elemental composition, and coating structure were explored by field emission scanning electron microscopy combined with energy-dispersive X-ray spectrometry and X-ray diffractometer. The deposition rate, microhardness, crystallite size and crystallinity index have also been investigated. The result of this study reveals that an experiment with low phosphorous content provides 6 times more microhardness. Thiourea was showing improved stabilizer characteristics and the EDX result confirms the presence of cerium in the coating. XRD analysis reveals some crystallinity in the coated samples.